Analisis Kerusakan Swing Machinery Excavator Kelas 125 Ton menggunakan Metode Root Cause Analysis - Abednego Sumarsono; Widia Setiawan; Nugroho Santoso; Harjono Harjono; Braam Delfian (Jurnal Material Teknologi Proses, 2026)
This study investigates the premature failure of swing machinery in a post-rebuild 125-ton excavator using a Root Cause Analysis (RCA) approach. The unit operated for only 3,642 service hours (HM), far below the fleet average of 18,872 HM. Three analytical methods were applied: Ishikawa Diagram, 5 Whys, and Fault Tree Analysis (FTA). Findings reveal that the failure originated from three interacting factors. First, swing bearing clearance was installed at 3.4 mm, exceeding the allowable range of 0.5–2 mm. Second, the excessive clearance caused misalignment between the pinion shaft gear and swing circle, producing edge loading and uneven load distribution across the contact surface. Third, repeated jack swing actions at the same position without component disassembly further concentrated the load. The progressive interaction of these factors triggered concentrated chipping, shaft deflection, and ultimately torsional fatigue fracture. Lubrication and contamination were eliminated as contributing causes, as oil analysis program data confirmed normal conditions throughout the operating period. This study highlights the critical importance of strict adherence to installation standards and proper operational response procedures in preventing premature failure of post-rebuild components.